Family Resilience Belief System: A Phenomenological Study on Javanese and Sundanese Family - Munawaroh, Eem; Sugiharto, D. Y. P.; Sofyan, Afriyadi; Ainata, Firdian Setiya; Asti, Zahra Permata Budi; Mashudi, Esya Anesty (Jurnal Kajian Bimbingan dan Konseling, 2021)
The purpose of this study was to determine family resilience based on the belief system in families with Javanese and Sundanese cultural backgrounds. The method used in this study is a qualitative phenomenological method. Phenomenological studies are used to understand phenomena at the level of subjective reality. Respondents in this study were five families with Javanese ethnic background domiciled in Kebumen and Banyumas regencies, Central Java and three families with Sundanese cultural background domiciled in Pangandaran and Sumedang regencies, West Java. The data collection method using in-depth interviews based on the concept of family resilience from Walsh describes three aspects of the belief system. The research data was analyzed using the Miles and Huberman model, which consists of three stages: data reduction, data presentation, and drawing conclusions with the help of qualitative data analysis software, namely Nvivo 12 Plus. The results show that families with Javanese and Sundanese backgrounds have a belief system in facing life’s trials which are manifested in the ability to interpret life’s difficulties, have a positive outlook, and the value of religiosity. The results of this study can be used as part of an assessment in schools and information on family resilience can be used as a counselor’s consideration in implementing family counseling and multicultural counseling services.